Unpacking Chinese EFL teachers’ TPACK challenges in online teaching - Gao, Yanjun; Teo, Timothy; Wong, Su Luan; Geng, Jingxin; Diao, Fangfang (SAGE Publications, 2026)
The integration of online teaching into higher education necessitates a deep understanding of the sustained challenges teachers face. This qualitative study investigates the Technological Pedagogical Content Knowledge (TPACK) challenges encountered by Chinese university-level English as a Foreign Language (EFL) teachers in their online practice. Data collected through semi-structured interviews with 10 teachers were analyzed thematically using the TPACK framework as a diagnostic lens. The findings reveal that the core impediments reside not in isolated knowledge domains but in the integrative components of TPACK. Specifically, teachers faced significant difficulties in Technological Pedagogical Knowledge (TPK), struggling to design meaningful communicative activities and to monitor student engagement effectively online. Concurrently, they encountered substantial challenges in Technological Content Knowledge (TCK), including sourcing level-appropriate digital materials and managing cumbersome workflows across fragmented platforms. The study concludes that a deficit in synthesizing technological, pedagogical, and content knowledge underpins these struggles. It underscores the need for targeted professional development that moves beyond technical training to explicitly foster the integrative capacities essential for effective online language teaching.